SPECTRUM OF RENAL ALLOGRAFT BIOPSY FINDINGS IN RENAL TRANSPLANT PATIENTS AT A TERTIARY CARE CENTER IN RAWALPINDI, PAKISTAN - Mansoor, Khurram; Osama, Muhammad; Ishaque, Muhammad; Sabir, Sohail; Din, Hafeez ud; Asif, Muhammad; Sabir, Haroon (Pakistan Armed Forces Medical Journal, 2021)
Objective: To evaluate outcome of diagnostic kidney biopsy in patients with renal allograft dysfunction at a tertiary care hospital.Study Design: Retrospective observational study.Place and Duration of Study: Armed Forces Institute of Urology, Rawalpindi, from Jan 2014 to Jan 2020.Methodology: A consolidate registry review was carried to formulate this study. The registry data exists at our center containing information about the graft dysfunction (manifesting as proteinuria, deranged urea and creatinine or urine sediment abnormalities) and other major indications which warrant probing with biopsy. The histopathological diagnosis of these biopsies is confirmed from the nephro-pathology registry before finalization of diagnosis.Results: A total of 94 diagnostic kidney biopsies were performed in patients with graft dysfunction. Out of 94 biopsies, 80 (85.1%) patients were male while 14 (14.9%) were female patients. The most frequent single cause for graft dysfunction was Cell Mediated Rejection (n 12, 24.5%) followed by Interstitial Fibrosis and Tubular Atrophy/Acute Tubular Injury. The most common cause among the glomerulonephritis was Membranoproliferative Glomerulonephritis (n 3, 6.1%) followed by others. The most common cause for mixed pathology remainedcell mediated rejection with Interstitial fibrosis and tubular atrophy (n 8, 17.8%).Conclusion: Cell mediated rejection is thecommonest pathology responsible for renal allograft dysfunction both as a single lesion as well as part of mixed pathology.